Diabetes and calcific aortic valve disease: controversy of clinical outcomes in diabetes after aortic valve replacement - Liu, Feng; Cai, Haipeng (Frontiers in Endocrinology, 2025)
Calcific aortic valve disease (CAVD) is a progressive disease, of which the 2-year mortality is >50% for symptomatic aortic valve stenosis unless transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR) is performed promptly. The prevalence of diabetes among CAVD has increased rapidly in recent years. The combination of diabetes with its cardio-renal and metabolic comorbidities, such as hypertension, hyperlipidemia, chronic kidney disease, and ageing, accelerated the progression of CAVD and increased the subsequent needs for aortic valve replacement. Clinical data regarding the impact of diabetes on outcomes of patients undergoing TAVR or SAVR have exhibited inconsistent results. Compared with non-diabetes, the short-term mortality after TAVR was not significant in diabetes, while the mid-term mortality differed from different cohorts. Although there were worse mid-term and long-term mortalities after SAVR in diabetes, the short-term mortality in diabetes was disputable. As for complications, there were common worse manifestations with coronary heart disease, acute kidney injury, heart failure, and systemic inflammatory response syndrome in diabetes undergoing TAVR or SAVR. Moreover, diabetes was one of the risk factors for deterioration of bioprosthetic aortic valves, leading to increased long-term mortality. Based on the efficacy for CAVD and atherosclerotic cardiovascular disease, glucose-lowering medications might have potential to inhibit deterioration of bioprosthetic aortic valves independent of glucose control.